Bioremediation of crude oil waste contaminated soil using petrophilic consortium and Azotobacter sp. - Fauzi, M; Suryatmana, P (Journal of Degraded and Mining Lands Management, 2016)
This study was aimed to determine the effect Petrophilic and Azotobacter sp. consortium on the rate of degradation of hydrocarbons, Azotobacter growth, and Petrophilic fungi growth in an Inceptisol contaminated with crude oil waste originating from Balongan refinery, one of Pertamina (Indonesia’s largest state-owned oil and gas company) units in Indramayu – West Java. This study was conducted from March to April 2014 in the glasshouse of research station of the Faculty of Agriculture, Padjadjaran University at Ciparanje, Jatinangor District, Sumedang Regency of West Java. This study used a factorial completely randomized design with two treatments. The first treatment factor was Petrophilic microbes (A) consisting of four levels (without treatment, 2% Petrophilic fungi, 2% Petrophilic bacteria, and the 2% Petrophilic consortium), and Azotobacter sp. The second treatment factor was Azotobacter sp. (B) consisting of four levels (without treatment, 0.5%, Azotobacter sp., 1% Azotobacter sp., and 1.5% Azotobacter sp.) The results demonstrated interaction between Petrophilic microbes and Azotobacter sp. towards hydrocarbon degradation rate, but no interaction was found towards the growth rate of Azotobacter sp. and Petrophilic fungi. Treatments of a1b3 (2% consortium of Petrophilic fungi with 1.5% Azotobacter sp.) and a3b3 (2% Petrophilic consortium and 1.5% Azotobacter sp.) had hydrocarbon degradation rate at 0.22 ppm/day for each treatment, showing the highest hydrocarbon degradation rate.